The Social Meaning of Kim Nam Jun’s Speech at UN General Assembly - Vivi Novalia Sitinjak; Kevin Gideon Barus; Jessica Anastasia Kianlin; Rainy Agria Agnes; Rinny Sherina Putri (English Education Study Program Faculty of Teacher Training and Education, 2023)
Kim Nam Jun (RM) the leader of BTS who spoke conveyed the contents of his speech representing the other six personnel. Speak Yourself is an inspiring giving activity for teenagers and young people around the world. This study aims to find out and analysis the social meaning of the speech by Kim Nam Jun. This study used the descriptive qualitative method. This researchs only focuses on Kim Nam Jun's speech to find the social meaning. The analysis found that Kim Nam Jun's speech contained data that matched the research criteria. The data is in the form of text in speech transcripts. Speech has 784 words. In analysis the data, the researchs read the transcript in the form of a speech text via the website and then determine and analysis social meaning contained in the speech. Then, describes the results of the analysis based on Geoffrey Leech's theory and can then make conclusions regarding the researchs results. The results also show Kim Nam Jun's speech that there is a social meaning to giving people the opportunity to express opinions, be confident, and do all the things they want to do.